The Challenges Faced by Indonesian Diaspora Teachers in Applying a Religious Psychology Approach to Teaching at Sangkhom Islam Wittaya School, Thailand - Qudratullah, Qudratulah; Samsinar, Samsinar; Yauri, Andi Muhammad; Wardana, Wardana; Abidin, Kurniati; Aziz, Muhammad Bachtiar (DIDAKTIKA, 2025)
This study aims to reveal the challenges faced by Indonesian diaspora teachers in applying a religious psychology approach to teaching at Sangkhom Islam Wittaya School, Thailand. Using a qualitative approach, this research employs a case study method involving observation, in-depth interviews, and document analysis. The research subjects consist of Indonesian diaspora teachers teaching at the school. The results show that teachers face challenges in the form of cultural differences, language barriers, adaptation to the local curriculum, and difficulties in integrating religious values with students' educational needs. Additionally, support from the school and local community plays a crucial role in helping teachers overcome these challenges. This study contributes to the development of more effective teaching strategies for Indonesian diaspora teachers, especially in religious-based schools abroad.Â